Assessing the Complementarity of Microtransit and Public Transit for Sustainable Mobility: Evidence from Three California Cities - Susan Shaheen; Elliot Martin; Brooke Wolfe; Cal Holman; Amartya Kumar (Sustainability, 2026)
Microtransit services fill gaps within public transportation systems across the United States (U.S.), but there are questions about whether they complement and compete with fixed-route services. The successful integration of microtransit is important for sustainability because it has the potential to improve the ridership and viability of public transit, which has implications for reducing emissions and increasing vehicle occupancy. Moreover, microtransit may serve as a more cost-effective way to provide transit service in low-density regions, relative to fixed-route services. We analyzed survey and trip activity data from three microtransit operations in California, including the Silicon Valley Hopper (N = 457), Richmond Moves (N = 131), and the Via West Sac (N = 224). For the Bay Area systems, surveys were deployed in November 2024, while activity data spanned June 2022 to November 2024. Via West Sac is one of the oldest microtransit systems in the U.S., and data from a May 2019 survey was integrated into the analysis. The survey showed that 35% of Richmond Moves, 31% of Silicon Valley Hopper, and 17% of Via West Sac respondents connected to and/or from public transit during their most recent microtransit trip. We estimated travel and wait times were lower on microtransit than public transit for 53% of Richmond Moves, 83% of Silicon Valley Hopper, and 85% of Via West Sac trips. We also found that 27% of Richmond Moves, 37% of Silicon Valley Hopper, and 52% of Via West Sac trips had no viable fixed-route transit alternative. Insights from these findings and expert interviews were used to define planning and design recommendations to improve complementarity. Key recommendations include providing comparative travel time information between microtransit and public transit options, highlighting faster fixed-route alternatives to requested trips, and offering transfer credits for microtransit trips that connect to transit.